THE POSSIBILITY OF USING ARTIFICIAL INTELLIGENCE IN LEGAL PROCEEDINGS OF CONTEMPORARY RUSSIA - Pshava, Veronika; Babenko, Irina; Pletnev, Vyacheslav; Sokolov, Aleksandr; Primak, Yana (Revista Inclusiones, 2020)
The research deals with the analysis of artificial intelligence as an integral part of the contemporary effective activity of judicial bodies, which, despite all the positive aspects of its functioning, is not a reason for rejecting the activities of officials in the judicial practice. The purpose of studying the possibilities of implementing artificial intelligence in the legal proceedings of contemporary Russia and the prospects for its application in this area is directly related to the need to develop and improve the regulatory framework. The analysis of modern scientific views on the possibility of using artificial intelligence in Russian court proceedings shows that there are opposed opinions concerning the forms and prospects of such use – from solving purely technical problems as an intelligent electronic assistant to the judge to replacing completely the judge in the administration of justice. According to the authors, at the present development stage of the Russian state, it is too early to talk about replacing the judge with artificial intelligence, while in the context of individual situations, it is impossible. The article compares examples of using the capabilities of artificial intelligence in the judicial activity of foreign countries and analyzes the main provisions of international acts that enshrine the ethical principles of the use of artificial intelligence in the judicial systems of European countries. In this article, the authors think about the prospects for implementing artificial intelligence in court proceedings of contemporary Russia, its effectiveness, as well as methods and approaches to this process, noting both beneficial and negative aspects of such implementation.